Enhancing Teacher Self-Management and Skills in Designing Teaching Materials through a Merdeka Curriculum Workshop at Muhammadiyah 1 Sleman Vocational High School - Syah, Arga Bagus Pratama Dyah Aan Firman; Suwarta; Siswanto, Deny Hadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This program aims to enhance teacher self-management and competence in developing teaching materials for the merdeka curriculum. The activity consists of three stages: pre-activity, implementation, and monitoring and evaluation. The training, which includes theoretical material, practical sessions, and relevant tests, was attended by 34 teachers from Muhammadiyah 1 Sleman Vocational High School and took place from July 8 to 9, 2024. The results indicated an improvement in teacher self-management and competence in developing teaching materials, with the average total percentage increasing from 70.17% on the Pre-Test to 80.44% on the Post-Test. For future training, it is recommended to focus more on participant motivation to enhance the effectiveness of the workshop, reduce delays, and further integrate learning and assessment in line with the merdeka curriculum.